RURAL TOURISM - AN ECONOMIC ALTERNATIVE FOR DEPOPULATED VILLAGES IN ROMANIA - CIPRIAN NIMARĂ (Annals of the University of Petrosani: Economics)
Romania has the greatest share of rural population in the European Union and according to the statistics, the risk for extreme poverty is four times higher in rural areas than in urban areas; also the depopulation trend is found in most rural areas. Romania has a rich natural and cultural potential in rural areas, which is a great advantage for attracting tourists to rural tourism and agro-tourism. The development of private property in Romania, after 1990, has led to an increase in accommodation capacity in agro-tourist boarding houses. This increase is due to the demand for holidays in rural areas, especially the demand from foreign tourists. The aim of this paper is to reveal a few proposals for an economic alternative of the depopulated villages through the revival imposed by rural tourism.